2016
DOI: 10.1021/jacs.6b01498
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cation and Neutral Radical of Aza-thia[7]helicene with SOMO–HOMO Energy Level Inversion

Abstract: We report a relatively persistent, open-shell aza-thia[7]­helicene with cross-conjugated electron-rich π-system. The singly occupied molecular orbital (SOMO) energy levels of both radical cation and neutral radical of the [7]­helicene are below the highest occupied molecular orbital (HOMO) energy levels, thereby violating the Aufbau principle. The aza-thia[7]­helicene is prepared from β-hexathiophene by a three-step one-pot reaction, in which the pyrrole ring is constructed by two consecutive C–N bond formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 52 publications
7
87
0
Order By: Relevance
“…8,14 To improve the stability of radical molecules, a common and effective approach is to shield the radical site by using bulky substituents; 16,17 another strategy is to increase the delocalization of the unpaired electron over a large segment of the backbone. 18,19 A recent focus of research on organic radicals considered the violation of the Aufbau principle, which was initially introduced by Niels Bohr in 1923 20 and dictates that 'a maximum of two electrons are put into orbitals in the order of increasing orbital energy' 21 ; violating the Aufbau principle of orbital occupation [22][23][24][25][26] has led to tremendously enhanced stability. 26 In the case of radicals with a non-Aufbau electronic structure, the singly occupied molecular orbital (SOMO) lies below the doubly occupied highest occupied molecular orbital (HOMO), namely, there occurs a SOMO-HOMO conversion/inversion (also referred to as a quasi-closed-shell system).…”
mentioning
confidence: 99%
“…8,14 To improve the stability of radical molecules, a common and effective approach is to shield the radical site by using bulky substituents; 16,17 another strategy is to increase the delocalization of the unpaired electron over a large segment of the backbone. 18,19 A recent focus of research on organic radicals considered the violation of the Aufbau principle, which was initially introduced by Niels Bohr in 1923 20 and dictates that 'a maximum of two electrons are put into orbitals in the order of increasing orbital energy' 21 ; violating the Aufbau principle of orbital occupation [22][23][24][25][26] has led to tremendously enhanced stability. 26 In the case of radicals with a non-Aufbau electronic structure, the singly occupied molecular orbital (SOMO) lies below the doubly occupied highest occupied molecular orbital (HOMO), namely, there occurs a SOMO-HOMO conversion/inversion (also referred to as a quasi-closed-shell system).…”
mentioning
confidence: 99%
“…This suggests that the reactivity of 3 .+ and 4 .+ caused by radical polymerization decreases as the energy level of the orbital containing the unpaired electron is buried deeper. Recently, a radical cation system with a SOMO‐HOMO energy inversion has received attention despite its cause not having been clarified . This system is believed to propose a new approach that indicates a similar phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Further, A. Rajca and co-workers prepared an analogous aza-thia[7]helicene 9 ( Figure 2, Table 2), wherein the central thiophene of 8 is replaced with pyrrole, with the aim of obtaining its cation radical and neutral radical. [24] The neutral aminyl radical of 9 was obtained by oxidation with [NO][PF 6 ] in the presence of large excess of a weak base (Cs 2 CO 3 ) at 195 K. The half-life of the neutral radical was estimated to be 8 � 3 h at room temperature under inert atmosphere. Notably, the DFT calculations of both cation and neutral radicals indicated that the SOMO energy levels were lower than the doubly occupied HOMO energy levels, which do not obey the Aufbau rule.…”
Section: Cation Radicals Of Helicenesmentioning
confidence: 99%